The Analysis Of Micromechanic On Creating Of Gypsum Board Strengthened By Bintaro Fruit Fiber (Cerbera Manghas) With 3d Orientation - Tri Adelia; delovita vita ginting; Romi Fadli Syahputra (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
This research succeeded in modifying the manufacture of gypsum board with the addition of natural fiber, namely bintaro fruit with the 3D orientation arrangement method. The raw materials for this research are gypsum flour and Bintaro fruit fiber as a matrix and filler. Bintaro fruit fiber previously carried out an alkalization process where the fiber was soaked in a solution of NaOH and distilled water for 24 hours. The manufacture of composites using the ratio of the matrix mass fraction and the filler mass fraction is as follows 100: 0, 99: 1, 98: 2 and 97: 3. The characterizations carried out include density test, moisture content test, flexural strength test and micromechanical analysis. Gypsum board composite based on micromechanical calculations resulted in the highest density value in the control sample, in the best density value was at the filler fraction of 3%, the best moisture content value in the control sample, the flexural strength test value the best of the control sample, but the filler fraction is 3% of the sample with the best fracture resistance. 3D orientation in theory and practice has fulfilled the principle that it is able to increase the physical and mechanical value of gypsum board.